17.3: D‐CIELAB: A Color Metric For Dichromatic Observers. Issue 1 (June 2015) - Jiang, Haomiao; Wandell, Brian A.; Farrella, Joyce E.
Abstract : A color metric for dichromatic subjects is proposed and evaluated empirically. The color metric extends the widely used CIELAB color difference metric, an international standard for trichromatic observers. The dichromatic extension (D‐CIELAB) is implemented by specifying a linear transformation that maps the two types of cone absorptions in dichromats to the three types of cone absorptions in trichromats and then applies the standard CIELAB color metric to these values. The linear mapping is derived from between‐eye color‐matches of observers who are dichromatic in one eye and trichromatic in the other eye. We evaluate the accuracy of the D‐CIELAB metric by predicting and measuring color discrimination thresholds for two dichromatic observers.